Application of Media Learning English Based on Flash for Second Graders at SD/MI (Case Study: MI Muhammadiyah 08 Kandangsemangkon Paciran) - Ulfa Yuliasari (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2017)
Computer could be use of the most important learning and more to be used, especially for multimedia learning based on computer will help for teachers and students. The purpose of research is to created interactive learning application and to provided a more affective and efficient learning opportunity.One of learning media that could assist to delivered a lesson is an interactive media with the education game in the media. This media to introduced technology and communications sets of equipment to students. In addition, it is could to try to do something as quickly of student about technology in education world.This application could used in second grade of elementary school. The menu are interested appearing include the content is for to introduced a letter, numbers, animals, and it’s sounds, games and quiz.